Whitewater kayaking : the ultimate guide - Whiting, Ken. (Heliconia Press, 2012)
This comprehensive guide covers everything from the most basic skills and concepts to the most advanced, cutting edge paddling techniques. Now in its second edition, Whitewater Kayaking has become the established, definitive guide on the sport.